2010
DOI: 10.1080/00131881003588097
|View full text |Cite
|
Sign up to set email alerts
|

Bullying among primary school children in New Zealand: relationships with prosocial behaviour and classroom climate

Abstract: Background: Bullying is a problem for schools in many countries, especially, according to various surveys, in New Zealand. Students' involvement in bullying as bullies, victims or bystanders has serious implication for emotional, social and academic development. Purpose: The purpose of this research was to examine the relationships between bullying, victimisation, prosocial behaviour, and classroom climate. A secondary purpose was to examine the use of the Peer Relations Questionnaire in New Zealand. Sample: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 30 publications
(32 reference statements)
8
56
2
7
Order By: Relevance
“…Group comparisons between bullies, victims, bully/victims (who bully others and are victimized themselves), and noninvolved children (neither bully nor victim) were less conclusive (van Noorden et al, ). In one study bullies reported less affective empathy than was reported by victims, and bully/victims reported less affective empathy than was reported by victims and by noninvolved peers (Raskauskas, Gregory, Harvey, Rifshana, & Evans, ). In another study victims reported more cognitive empathy than was reported by noninvolved peers, whereas victims did not differ from bullies and bully/victims (Williford, Boulton, & Jenson, ).…”
Section: Bullying Involvement and Empathymentioning
confidence: 99%
“…Group comparisons between bullies, victims, bully/victims (who bully others and are victimized themselves), and noninvolved children (neither bully nor victim) were less conclusive (van Noorden et al, ). In one study bullies reported less affective empathy than was reported by victims, and bully/victims reported less affective empathy than was reported by victims and by noninvolved peers (Raskauskas, Gregory, Harvey, Rifshana, & Evans, ). In another study victims reported more cognitive empathy than was reported by noninvolved peers, whereas victims did not differ from bullies and bully/victims (Williford, Boulton, & Jenson, ).…”
Section: Bullying Involvement and Empathymentioning
confidence: 99%
“…An extensive body of research evidence confirms that positive, respectful and supportive teacher-student relationships contribute to a wide range of desirable student outcomes linked to wellbeing such as attendance (Klem and Connells 2004); engagement and high levels of achievement motivation (e.g.Hattie 2009; Klem and Connell 2004;Martin et al 2007;Marzano 2003;Roorda et al 2011);and resilience (Battistich et al 2004;Nadel and Muir 2005;Raskauskas et al 2010;Weare 2000). Student behaviour and choices are more likely to be positively influenced by the behaviour and values of trustworthy teachers who provide a secure base (Masten and Obradović 2008).…”
Section: Positive Teacher-student Relationshipsmentioning
confidence: 99%
“…In addition, it is suggested that good relationships between teachers and students give the students the confidence to report bullying to their teachers and provide the teachers with the opportunity to intervene appropriately (Maunder and Tattersall, ). A number of researchers point out that a good relationship between teacher and students is vital in terms of preventing and reducing bullying (Allen, ,b; Newman‐Carlson and Horne, ; Raskauskas and others, ; Rodkin and Hodges, ).…”
Section: Resultsmentioning
confidence: 99%